Herpetofauna of the quaternary sand dunes of the middle Rio São Francisco, Bahia, Brazil: VIII. Amphisbaena arda sp. nov., a fuliginosa-like checkered patterned Amphisbaena (Squamata, Amphisbaenidae) - Miguel Trefaut Rodrigues (Phyllomedusa: Journal of Herpetology, 2002)
Amphisbaena arda sp. nov. is described based on a specimen obtained at Mocambo do Vento, on the left bank of the São Francisco river, Bahia State, Brazil. A. arda is a medium sized amphisbaenian with a checkered black and white color pattern similar to the one present in the fuliginosa group but differing from that by having a lighter pigmentation, an uniformly white ventral surface, and by several other important morphological characters. A. arda is similar to Amphisbaena vermicularis in meristic characters currently used to assist amphisbaenian identification but can be separated from it by its color pattern, its flatter cephalic shields, and by the more ventral position of nostril.